Climatic change and fire potential in South‐Central British Columbia, Canada - CRAIG R. NITSCHKE; JOHN L. INNES (Global Change Biology, 2008)
The incidence and severity of forest fires are linked to the interaction between climate, fuel and topography. Increased warming and drying in the future is expected to have a significant impact on the risk of forest fire occurrence. An increase in fire risk is linked to the synchronous relationship between climate and fuel moisture conditions. A warmer, drier climate will lead to drier forest fuels that will in turn increase the chance of successful fire ignition and propagation. This interaction will increase the severity of fire weather, which, in turn, will increase the risk of extreme fire behaviour. A warmer climate will also extend fire season length, which will increase the likelihood of fires occurring over a greater proportion of the year. In this study of the North Okanagan area of British Columbia, Canada, the impacts of climate change of fire potential were evaluated using the Canadian Forest Fire Danger Rating System and multiple climate scenario analysis. Utilizing this approach, a 30% increase in fire season length was modelled to occur by 2070. In addition, statistically significant increases in fire severity and fire behaviour were also modelled. Fire weather severity was predicted to increase by 95% during the summer months by 2070 while fire behaviour was predicted to shift from surface fire‐intermittent crown fire regimes to a predominantly intermittent‐full crown fire regime by 2070 onwards. An increase in fire season length, fire weather severity and fire behaviour will increase the costs of fire suppression and the risk of property and resource loss while limiting human‐use within vulnerable forest landscapes. An increase in fire weather severity and fire behaviour over a greater proportion of the season will increase the risks faced by ecosystems and biodiversity to climatic change and increase the costs and difficulty of achieving sustainable forest management.